PENGEMBANGAN ALAT UKUR MULTIPLE INTELLIGENCE UNTUK PENELUSURAN MINAT DAN BAKAT SISWA SMA - Farida Agus Setiawati (Universitas Negeri Yogyakarta, 2008)
This study is brought about from three main reasons; namely the rise of the theory of multiple intelligence, students' inability tounderstandtheir talents and interests, and absence of a standardized instrumentof multiple intelligence. Based on these concerns, this study is aimed at developing an instrument useful to disclose the multiple intelligenceprofiles of students of the senior high school in Indonesia. Thestudy uses the quantitative approach. Data collecting processes, however,are supported by the qualitative method. The subjects of this researchare students of the senior high school in Daerah Istimewa Yogyakartatotalling at 920 students. Quantitative data collection is carriedout by the instrument and then the data are analized using the SPSSprogram package. Qualitative data collection is done through discussions and expert judgements. Using a content validity test as the measure for validity, a model of the instrument of the multiple intelligenceis developed to measure the tendencies of the senior high school students' interests and talents. The instrument is divided into twoparts. Thefirst is to measure the students' talents and the second is to measure the students' interests. Using the item selection technique for the measure of reliability, the realibility of test is represented by the coefficient count of 0.9044 for scale I and 0.6789for scale 2. These results show that this instrument is valid and realible